ANALISIS KOMPETENSI PROFESIONAL GURU GEOGRAFI SMA NEGERI DAN SWASTA KABUPATEN PRINGSEWU - Nur Hayati; Zulkarnain Zulkarnain; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2015)
The analysis of professional competency geography teachers is expected to knowprofessional competency. This research used descriptive method. The population of this research 25 geography teachers. Data collection technique of this research was conducted by using test technique, observation and documentation. The technique of analysis data used a percentage. The results of research showed that professional competency of geography teacher whave low criteria, with indicator : (1) the most of geography teacher have the ability of materials comprehensionwith enough criteria, (2) the most of geography teacher have the ability in sustainable professional development with lesscriteria, (3) the most of geography teacher have the ability in utilizing of ITC with enough criteria, (4) the most of geography teacher have the ability of mastering standard competence and the core competence with lesscriteria, (5) the most of geography teacher have the ability in development of materials with lesscriteria.Melalui analisis kompetensi profesional guru geografi diharapkan dapat diketahui kompetensi profesional. Penelitian ini menggunakan metode deskriptif. Penelitian ini penelitian populasi yaitu seluruh guru geografi sebanyak 25. Pengumpulan data dilakukan dengan melakukan teknik tes, observasi, dan dokumentasi. Teknik analisis data menggunakan presentase. Hasil penelitian menunjukkan bahwa kompetensi profesional guru geografi masih kurang, dengan indikator sebagai berikut: (1) memiliki kemampuan penguasaan materi dengan kriteria cukup, (2) memiliki kemampuan pengembangan profesional berkelanjutan dengan kriteria kurang, (3) memiliki kemampuan pemanfaatan TIK dengan kriteria cukup, (4) memiliki kemampuan penguasaan standar kompetensi dan kompetensi dasar dengan kriteria kurang, (5) memiliki kemampuan pengembangan materi dengan kriteria kurang.Kata kunci: kompetensi profesional, guru geografi, sma negeri dan swasta.